ANALISIS PENDAPATAN BAGI HASIL PAJAK PROVINSI SEBAGAI UPAYA PENINGKATAN PEMBANGUNAN DAERAH (STUDI PADA DINAS PENDAPATAN DAERAH DAN BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN KEDIRI TAHUN 2008-2013) - Maharani, Novia Ratna (Jurnal Mahasiswa Perpajakan, 2014)
The purpose of this research is to know the target, realization and the growth of split profits income of Provincial Taxes in Kediri, and also to know the regional needs addiction level of that acceptance and the contribution of that income for regional development in Kediri from 2008 to 2013. The method of this research is descriptive research. The result of this research shows that the target of provicial taxes split profit income in 2008-2011 and 2013 has been reached, but in 2012 the target can not be reached. From 2008 to 2013, the split profits income of Provincial Taxes in Kediri went up gradually and fell once only in 2012. Regional needs addiction level of that income fluctuate and it’s value was 5,31% in average, from 2008 to 2013. The contribution of that income for Financial Expenditure fluctuate and it’s value was 30,35% in average from 2008 to 2013. Keywords: Provincial Taxes, Split Profits Income of Provincial Taxes, Regional Development